Thursday

April 17, 2014

April 17, 2014

Posted by **Aliza** on Monday, December 10, 2012 at 8:52am.

*CHALLENGE.

1.SIMPLIFY : SQUARE ROOT OF 16^8+8^4/16^2+16^7

2.EXPRESS 1 + 1/1+SQUARE ROOT OF 2 - 1/1-SQUARE ROOT OF 2 IN THE FORM A+B SQUARE ROOT OF 2, WHERE A AND BARE RATIONAL NUMBERS. FIND A + B.

3. ARRANGE THE NUMBERS- SQUARE ROOT OF 6, 1+ SQUARE ROOT OF 2, 2 SQUARE ROOT OF 5/3 IN INCREASING ORDER WITHOUT THE USE OF CALCULATOR.

4. WHAT IS THE POSITIVE GEOMETRIC MEAN FOR THE POSITIVE DIVISORS OF 2012?

5. WHAT IS THE SIMPLEST FORM OF 12/SQUARE ROOT OF 2 + SQUARE ROOT OF 3 + SQUARE ROOT OF 5?

6. A CUBE IS INSCRIBED IN A SPHERE WHOSE DIAMETER IS 12 CM. WHAT IS THE VOLUME OF THE CUBE?

7. THE DIFFERENCE BETWEEN 2 POSITIVE NUMBERS IS 2 SQUARE ROOT OF 3 AND THE PRODUCT OF THE 2 NUMBERS IS SQUARE ROOT OF 2. FIND THE ABSOLUTE VALUE OF THE DIFFERENCE OF THEIR RECIPROCALS.

PLEASE ANSWER AS SOON AS POSSIBLE. PLEASEEEEE. WITH SOLUTIONS . HOW YOU DID IT PLEASEEEEEEEEE.

- Math PLEASE HELP ASAP -
**Steve**, Monday, December 10, 2012 at 11:13amwhew - hard to concentrate WITH ALL THE SHOUTING!!!

#1:

(16^8+8^4)/(16^2+16^7)

= (16^8+16^2)/(16^2+16^7)

= 16^2 (16^6+1) / 16^2 (1+16^5)

= (16^6+1)/(16^5+1)

don't see any way to simplify that, so you wind up with

√(16^6+1)/(16^5+1)

it will be very very close to √16=4

#2:

1/(1+√2) - 1/(1-√2)

put all over a common denominator

[(1-√2) - (1+√2)]/(1^2 - √2^2)

= -2√2/(1-2)

= 2√2

#3:

√6,1+√2,2√5/3

try squaring the values. The squares will be in the same order as the numbers:

6,3+2√2,20/9

3+3,3+2√2,3-7/9

Since √2 < 1.5, 3+2√2 < 3+3

Looks like they should be in order:

2√5/3, 1+√2, √6

#4:

2012 = 2^2 * 503

The divisors are thus

1,2,4,503,1006,2012

geometric mean is sixthroot(2012^3) = √2012 = 2√503

#5:

12/√2 + √3 + √5

= 6√2 + √3 + √5

Hmmm. not much sense

How about

12/(√2+√3+√5) = 3√2 + 2√3 - √30

not sure that's any simpler

#6:

The main diagonal of the cube is the diameter of the sphere. So, the side s of the cube is

3s^2 = 12

s=2

volume = 8

#7:

x-y = 2√3

xy = √2

1/x - 1/y = (y-x)/xy = -2√3/√2 = -√6

so, |1/x - 1/y| = √6

**Related Questions**

socials - can u please explain the methaphor "slow dawns are caught in great ...

Math ; please please help. - 1. Explain in detail how to determine the value of ...

Math - Please help!!!!!!!!!!! Find all solutions in the interval [0,2π). 7...

Math - Please explain how you got this answer as well! A shape has a perimeter ...

ASAP - can someone please make up an address and a phone number that i can use ...

math - Help pllsss ASAP!!! have certain answers!! i try but i do not understand...

Precalculus - Please help!!!!!!!!!!! Find all solutions in the interval [0,2&#...

Pre Algebra Help ASAP - Which of the following equations has an infinite number ...

Math - A cookie jar contains 3 chocolate-chip, 2 peanut butter, 1 lemon, 1 ...

algebra - How many solutions does the following system have: 6x - 3y = 9 2x - y...